Parotidectomy for Unilateral Pain Attributed to Sialosis - Evgeniya Molotkova; Piper Wenzel; Anand Rajan; Henry Hoffman (Clinical Case Reports)
ABSTRACT This case uniquely provides radiographic and histopathologic correlates offering insight into the poorly understood disorder of symptomatic sialosis (sialadeneosis). Sialosis is often managed conservatively, with surgical intervention reserved for symptomatic cases refractory to conservative management. The rarely employed surgical treatment is highlighted in this patient by relief of presenting symptoms accompanied by later complications.